PENGARUH JENIS DAN WAKTU APLIKASI PUPUK ORGANIK CAIR (POC) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN (Cucumis sativus L) - Nino, Jefrianus (Fakultas Pertanian, Sains, dan Kesehatan, Universitas Timor, 2025)
Cucumber (Cucumis sativus L.) is a vine that is generally consumed directly or in processed form. In Indonesia, there are still many who cultivate cucumbers in the conventional way and there are still many who use chemical fertilizers, but the expected results are not worth it so that many farmers who cultivate cucumbers eventually go out of business or go bankrupt. This proves that agricultural production that still uses chemicals will damage the soil texture. Efforts to reduce the excessive use of chemical fertilizers in increasing cucumber crop production include fertilizing using liquid organic fertilizers. This study aims to determine the effect of the use of liquid organic fertilizer banana weevil, tofu dregs, and banana peel on the growth and yield of cucumber plants (Cucumis sativus L.) and obtain the best type and time of application of liquid organic fertilizer for the growth and yield of cucumber plants (Cucumis sativus L.) This research will be conducted in August-September 2023, in Noebaun Village, Noemuti District, North Central Timor Regency. Field experiments using RAL factorial 3 x 3 were repeated 3 times. The first factor is the type of POC which consists of three treatments, namely POC banana weevil (P1), POC tofu pulp (P2) and POC banana peel (P3) with each POC treatment 20 ml / 10 L water. The second factor is the POC application time which consists of three treatments, namely POC application once every 1 week (O1), POC application once every 2 weeks (O2) and POC application once every 3 weeks (O3). So that there are 9 combinations of treatments, namely: P1O1, P2O1, P3O1, P1O2, P2O2, P3O2, P1O3, P2O3, P3O3 then there are 27 experimental polybags and 3 control polybags so that there are 30 experimental units. The results of the study stated that there was a real influence on the growth and yield of cucumber plants. This can be seen with the highest value for the parameters of soil acidity (pH 5.84), number of internodes 42 HST (11.11 internodes), fruit weight (350.86 grams), fruit length (20.09 cm), fruit diameter (26.71 mm). POC treatment of banana peel and application time once every 1 week is the best treatment in increasing cucumber growth and yield. This can be seen with the highest value for the parameters of soil acidity (pH 5.72), stem diameter 42 HST (0.42 mm), number of internodes (10.44 internodes), fruit weight (333.83 grams), fruit length (20.26 cm), fruit diameter (25.27 mm).